2018
DOI: 10.1016/j.bbrep.2018.07.001
|View full text |Cite
|
Sign up to set email alerts
|

BCL2 inhibitor ABT-199 and JNK inhibitor SP600125 exhibit synergistic cytotoxicity against imatinib-resistant Ph+ ALL cells

Abstract: Imatinib (IMT), a specific tyrosine kinase inhibitor (TKI), has drastically changed the treatment strategy for Ph+ ALL (Philadelphia chromosome-positive acute lymphoblastic leukemia). However, TKI resistance remains a serious problem for patient prognosis. Here, a Ph+ ALL cell line NphA2 and the IMT-resistant subline NphA2/STIR were analyzed to identify a potential novel treatment strategy. We also examined other Ph+ ALL cells, MR87 and its IMT-resistant subline, MR87/STIR. IMT induced apoptosis of NphA2 and M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…SCAPs at passage 2-5 were used in the subsequent experiments. To address the potential roles of JNK and ERK signaling pathways, specific JNK inhibitor (20 µ M; SP600125), specific ERK inhibitor (20 µ M; U0126; both from Beyotime Institute of Biotechnology) and dimethyl sulfoxide (20 µ M; Sigma-Aldrich; Merck KGaA, Darmstadt, Germany) as a control were respectively added to the SCAPs, and the cells were incubated at 37°C for 5 min ( 29 , 30 ). As for the characterization of cultured SCAPs, the cells were digested with trypsin (Roche Applied Science), collected and incubated with fluorochrome-conjugated rabbit anti-human antibodies: Cluster of differentiation (CD)90-fluorescein isothiocyanate (FITC; 561969), CD44-phycoerythrin (PE; 561858), CD45-allophycocyanin (560973) and CD14-PE-cyanine 7 (560919; all at 0.5 mg/ml; BD Biosciences, San Jose, CA, USA) for 1 h at 4°C in the dark to detect the SCAPs phenotype ( 31 , 32 ).…”
Section: Methodsmentioning
confidence: 99%
“…SCAPs at passage 2-5 were used in the subsequent experiments. To address the potential roles of JNK and ERK signaling pathways, specific JNK inhibitor (20 µ M; SP600125), specific ERK inhibitor (20 µ M; U0126; both from Beyotime Institute of Biotechnology) and dimethyl sulfoxide (20 µ M; Sigma-Aldrich; Merck KGaA, Darmstadt, Germany) as a control were respectively added to the SCAPs, and the cells were incubated at 37°C for 5 min ( 29 , 30 ). As for the characterization of cultured SCAPs, the cells were digested with trypsin (Roche Applied Science), collected and incubated with fluorochrome-conjugated rabbit anti-human antibodies: Cluster of differentiation (CD)90-fluorescein isothiocyanate (FITC; 561969), CD44-phycoerythrin (PE; 561858), CD45-allophycocyanin (560973) and CD14-PE-cyanine 7 (560919; all at 0.5 mg/ml; BD Biosciences, San Jose, CA, USA) for 1 h at 4°C in the dark to detect the SCAPs phenotype ( 31 , 32 ).…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, the combination of dasatinib and venetoclax resulted in superior antileukemic efficacy compared to either agent alone in Ph+ ALL xenografts (84). Another report showed that the combination of venetoclax and the JNK inhibitor SP600125 exhibited synergistic cytotoxicity against imatinib-resistant Ph+ ALL cells (85).…”
Section: Apoptosis Regulatorsmentioning
confidence: 99%
“…In this case, we included an p38 inhibitor (SB203580) [ 27 ] and a JNK inhibitor, SP600125 [ 28 ] in our analysis. According to previous studies, SP600125 (10 µM) was considered cytotoxic in different cell lines such as four different leukemia cell lines (U937, K562, HL60, and THP-1) [ 29 ], NphA2 cells [ 30 ], while SB203580 and SP600125 at 20 µM did not alter cell viability neither in MCF7 cells [ 31 ] nor in JEG-3 cells [ 32 ]. However, it is known that distinct cell lines respond differently to cytotoxic compounds.…”
Section: Resultsmentioning
confidence: 99%